Конструирование десублиматора для гексафторида урана и других летучих фторидов - Русаков И. Ю. Игорь Юрьевич; Буйновский А. С. Александр Сергеевич; Софронов В. Л. Владимир Леонидович; Дьяченко А. Н. Александр Николаевич (2010, 2010)
Заглавие с экрана